Very-Large-Scale Integration (IntechOpen, 2023)
In this book, a variety of topics related to Very-Large-Scale Integration (VLSI) is extensively discussed. The topics encompass the physics of VLSI transistors, the process of integrated chip design and fabrication and the applications of VLSI devices. It is intended to provide information on the latest advancement of VLSI technology to researchers, physicists as well as engineers working in the field of semiconductor manufacturing and VLSI design.